Impact of the use of curtains on the spatial distribution of the parameter definition (D50) in Brazilian classrooms - Kawakita Ikeda, Cristina Yukari; Vittorino , Fulvio; Ono, Rosaria (ENCONTRO NACIONAL DE CONFORTO NO AMBIENTE CONSTRUÍDO, 2023)
When the understanding of the spoken message is crucial, just some of the several of the acoustic descriptors used to evaluate the acoustic quality of rooms tend to attract more attention. The usage of curtains in Brazilian schools is a low-cost method typically used for solar protection, although their use might correct the values of the acoustic descriptors by getting these parameters within acceptable ranges. The spatial distribution of the definition (D50) parameter in classrooms with open and closed curtains is the main topic of this paper. Computer simulation was used to estimate the sound behavior. Reverberation time measured in the rooms was used to adjust the simulated classroom models. Two closed window arrangements, with open and closed curtains, were studied for the classrooms. In this study, the effect of opening the curtain was variable depending on the frequency, but for all the cases, higher values of D50 were obtained with the closing of the curtains. Since D50 is a parameter that can be modified by using sound absorption, the designers can make interventions to improve the homogeneity of the parameter spatial distribution.